AN ANALYSIS OF DERIVATIONAL AFFIXES IN THE AVENGERS MOVIE - Sumual, Merciana S.; Arifin, M. Bahri; Valiantien, Nita Maya (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2021)
This study aimed to discuss derivational affixes in The Avengers movie. Derivational affixes was interesting to analyze since it has affect in forming word from simple to more complex. By using descriptive method and qualitative approach, this study has purposes to identify characteristics applied in forming derived words and dictionary information that presented from those derived words in the movie. The data source was taken from The Avengers movie script, primary data were words undergo affixation in the movie script. The characteristics of derivational was analyzed by using Brinton & Brinton(2010) theory and supported theory by Fromkin(2011) in forming derivational affixes, then the dictionary information based on Jackson(1982) and Redman(1997). The result of this study showed that there were four general characteristics applied in forming derived words. First, all words undergo meaning change and word class change or one of those two changes. Second, each prefix and suffix has meaning to indicate new meaning of the base. Third, some words undergo orthographic change when suffix attach to base and change the base form. Fourth, some words undergo phonological change when suffix attach to base and change the pronunciation of the word. Next, all words have dictionary information such as Spelling, Pronunciation, Part of speech, Etymology, Definition, Example of phrase or sentence, Word Opposite, Common Collocation, Usage and Special grammatical. The most dictionary information found are Spelling, Part of speech and Definition.